Republic of Equatorial Guinea : First Review under the Staff-Monitored Program-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2018)
In May 2018, the IMF's Management approved a 7-month Staff-Monitored Program (SMP), covering the period January 1-July 31, 2018. The main fiscal objectives of the SMP are to (i) reduce the budget deficit through non-hydrocarbon revenue mobilization and expenditure reduction while protecting social spending and (ii) address critical weaknesses in public financial management. The program also contains measures to improve the business climate, foster economic diversification, and lay the basis for improving governance and transparency. In addition, the program is providing a framework for bolstering capacity and helping build an adequate track record of performance as the basis for discussions on a potential Fund-supported program later this year.